Image and knowledge, mimesis as a universal category - Gutiérrez Gómez, Alba Cecilia (Estudios de Filosofía, 1996)
There is a widespread opinion according to which since the XVIII century mimesis is no longer a paradigm of art. On the contrary, this article inspired on a basic idea of H. G. Gadamer, presents its prevalence starting from a review of the Greek text founding the theory of art and from other sources related to the evolution of mimesis as a concept in western aesthetics. Far from the modern distortion reducing mimesis to a mere replica of sensitive appearances, the original concept meant to make a parallel to nature. It is founded, on the one hand, on the pitagoric idea of universal order manifested in the movement of heavenly bodies as much as in the human soul and in the beauty of works of art, and on the other hand, on the aristotelean idea of "re-cognition" that sets aside what is non- essential.